Online Self-Administered Cognitive Testing Using the Amsterdam Cognition Scan: Establishing Psychometric Properties and Normative Data. - Feenstra, Heleen EM; Vermeulen, Ivar E; Murre, Jaap MJ; Schagen, Sanne B (Journal of Medical Internet Research, 2018)
Background: Online tests enable efficient self-administered assessments and consequently facilitate large-scale data collection for many fields of research. The Amsterdam Cognition Scan is a new online neuropsychological test battery that measures a broad variety of cognitive functions.Objective: The aims of this study were to evaluate the psychometric properties of the Amsterdam Cognition Scan and to establish regression-based normative data.Methods: The Amsterdam Cognition Scan was self-administrated twice from home-with an interval of 6 weeks-by 248 healthy Dutch-speaking adults aged 18 to 81 years.Results: Test-retest reliability was moderate to high and comparable with that of equivalent traditional tests (intraclass correlation coefficients: .45 to .80; .83 for the Amsterdam Cognition Scan total score). Multiple regression analyses indicated that (1) participants' age negatively influenced all (12) cognitive measures, (2) gender was associated with performance on six measures, and (3) education level was positively associated with performance on four measures. In addition, we observed influences of tested computer skills and of self-reported amount of computer use on cognitive performance. Demographic characteristics that proved to influence Amsterdam Cognition Scan test performance were included in regression-based predictive formulas to establish demographically adjusted normative data.Conclusions: Initial results from a healthy adult sample indicate that the Amsterdam Cognition Scan has high usability and can give reliable measures of various generic cognitive ability areas. For future use, the influence of computer skills and experience should be further studied, and for repeated measurements, computer configuration should be consistent. The reported normative data allow for initial interpretation of Amsterdam Cognition Scan performances.